Development of the Empowering Leadership Scale for Thai Educational School Administrators - Boonyota , Krittaphas; Thawinkarn, Dawruwan; Ketchatturat, Jatuphum (Journal of Ecohumanism, 2025)
The development of the Empowering Leadership Scale for Thai Educational School Administrators aimed to study the components and indicators of empowering leadership among Thai school administrators and to verify the construct validity of the empowering leadership model. Data were collected from 520 teachers and school personnel selected through a multi-stage sampling process. Confirmatory Factor Analysis (CFA) was employed, revealing that the model fit indices were χ² = 6.725, df = 3, p-value = .0812, RMSEA = .049, SRMR = .004, CFI = .999, and TLI = .996. These statistical values meet the established criteria, confirming the main hypothesis that the theoretical model aligns with empirical data. As a result, the Empowering Leadership Scale demonstrated construct validity and can be effectively used to measure the empowering leadership of Thai educational school administrators.